Industrial service engineering : training requirements for systematic service development - Fischer, Clemens (Array, 2020)
Increasing digitization and rising customer requirements represent an opportunity for companies in the machine- and plant engineering industry. For long-term success, combined packages of product and service must be offered, to gain additional revenues and a unique selling proposition. Basically, the advantages of these bundles are slowly establishing themselves in industrial companies. The problem is, that the development and improvement of these bundles run often unsystematically, without a strategy. In Austria, companies are facing the issue, that they are not able to develop new services, due to a shortage of specially skilled employees. This derives out of a lack of clear definition of educational requirements. In order to identify those gaps, an empirical investigation based on expert interviews was conducted and the current status of training requirements was defined. As a result, future service job profiles and potential trends for education and training in the service area of industrial companies were derived thus machine- and plant engineering companies can innovate their employee education strategy.